Prevalence of mild cognitive impairment and its association with malnutrition in older Chinese adults in the community - Wang, Ling-ying; Hu, Zi-yi; Chen, Hong-xiu; Zhou, Chun-fen; Hu, Xiu-ying (Frontiers in Public Health, 2024)
Objective: This study aims to characterize the prevalence and associated factors of cognitive impairment in older adults within Chinese community settings.Background: Research exploring the interrelation between malnutrition and cognitive impairment in the elderly community-dwelling population is scarce. The impact of nutritional status on cognitive function in aging adults has not been definitively established.: A cross-sectional survey was conducted in one urban and one rural community in Chengdu, China, from October 2022 to March 2023. The sample included 706 older adults. Logistic regression was utilized to determine independent risk factors for mild cognitive impairment (MCI).The study found a significant prevalence of MCI at 32.0% among the older adult population. Among those suffering from malnutrition, 55.6% were affected by MCI. The logistic regression analysis indicated that malnutrition risk (OR=2.192, 95% CI 1.431 to 3.357, P<0.001), rural residence (OR=1.475, 95% CI 1.003 to 2.170, P=0.048), age (70-79 years old; OR=2.425, 95% CI 1.611 to 3.651, P<0.001; ≥80 years old: OR=4.773, 95% CI 2.571 to 8.859, P<0.001), male (OR=1.584, 95% CI 1.085 to 2.313, P=0.017), middle education level (OR=0.986, 95% CI 1.627 to 5.482, P<0.001), and ADL dependence (OR=1.810, 95% CI 1.158 to 2.827, P=0.009) were significantly associated with the occurrence of MCI.The findings indicate a widespread occurrence of MCI in communitydwelling older Chinese adults. The association between malnutrition, as measured by the Mini Nutritional Assessment-Short Form (MNA-SF), and cognitive decline is evident. Elderly individuals with nutritional risk, advancing age, rural residence, male gender, moderate education, and ADL dependency are at increased likelihood of developing MCI. Longitudinal research is needed to clarify the temporal relationships between MCI, demographic factors, and whether improvements in nutritional status or ADL can reduce the incidence of MCI in this population.